Trinidad, B.W.I. - (:unkn) unknown (Unknown, 2011)
The postcard bears the images of three places of interest around Trinidad:The Governor's residence, The Queen's Park Savannah and a country residence.
Colour: Coloured; Style: Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Historic sites; President's House, The; Queen's Park Savannah; Governor's residence, The